Mitigating the effects of COVID-19 on HIV treatment and care in Lusaka, Zambia: a before–after cohort study using mixed effects regression. Issue 1 (25th January 2022) - Pry, Jake M; Sikombe, Kombatende; Mody, Aaloke; Iyer, Shilpa; Mutale, Jacob; Vlahakis, Natalie; Savory, Theodora; Wa Mwanza, Mwanza; Mweebo, Keith; Mwila, Annie; Mwale, Consity; Mukumbwa-Mwenechanya, Mpande; et al.
Abstract : Introduction: The Zambian Ministry of Health (MoH) issued COVID-19 mitigation guidance for HIV care immediately after the first COVID-19 case was confirmed in Zambia on 18 March 2020. The Centre for Infectious Disease Research in Zambia implemented MoH guidance by: 1) extending antiretroviral therapy (ART) refill duration to 6 multi-month dispensation (6MMD) and 2) task-shifting communication and mobilisation of those in HIV care to collect their next ART refill early. We assessed the impact of COVID-19 mitigation guidance on HIV care 3 months before and after guidance implementation. Methods: We reviewed all ART pharmacy visit data in the national HIV medical record for PLHIV in care having ≥1 visit between 1 January—30 June 2020 at 59 HIV care facilities in Lusaka Province, Zambia. We undertook a before–after evaluation using mixed-effects Poisson regression to examine predictors and marginal probability of early clinic return (pharmacy visit >7 days before next appointment), proportion of late visit (>7 days late for next appointment) and probability of receiving a 6MMD ART refill. Results: A total of 101 371 individuals (64% female, median age 39) with 130 486 pharmacy visits were included in the analysis. We observed a significant increase in the adjusted prevalence ratio (4.63; 95% CI 4.45 to 4.82) of early return before compared with after guidance implementation. Receipt of 6MMD increased from a weekly mean of 47.9% (95% CI 46.6% to 49.2%) before to 73.4% (95% CI 72.0% to 74.9%) after guidance implementation. The proportion of late visits (8–89 days late) was significantly higher before (18.8%, 95% CI17.2%to20.2%) compared with after (15.1%, 95% CI13.8%to16.4%) guidance implementation . Conclusions: Timely issuance and implementation of COVID-19 mitigation guidance involving task-shifted patient communication and mobilisation alongside 6MMD significantly increased early return to ART clinic, potentially reducing interruptions in HIV care during a global public health emergency.